2019
DOI: 10.1002/anie.201911319
|View full text |Cite
|
Sign up to set email alerts
|

Negative Charge as a Lens for Concentrating Antiaromaticity: Using a Pentagonal “Defect” and Helicene Strain for Cyclizations

Abstract: Incorporation of a five‐membered ring into a helicene framework disrupts aromatic conjugation and provides a site for selective deprotonation. The deprotonation creates an anionic cyclopentadienyl unit, switches on conjugation, leads to a >200 nm red‐shift in the absorbance spectrum and injects a charge into a helical conjugated π‐system without injecting a spin. Structural consequences of deprotonation were revealed via analysis of a monoanionic helicene co‐crystallized with {K+(18‐crown‐6)(THF)} and {Cs+2(18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
51
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 40 publications
(59 citation statements)
references
References 115 publications
6
51
1
Order By: Relevance
“…Each K + ion is fully wrapped by two benzo-15-crown-5 ether molecules with the K/O crown distances (2.752(2)-2.945(2) A) being comparable to those previously reported. [51][52][53][55][56][57][58] Seven interstitial THF molecules are found to ll the structural voids with no close contacts.…”
Section: Crystal Structures and Supramolecular Packingmentioning
confidence: 97%
See 2 more Smart Citations
“…Each K + ion is fully wrapped by two benzo-15-crown-5 ether molecules with the K/O crown distances (2.752(2)-2.945(2) A) being comparable to those previously reported. [51][52][53][55][56][57][58] Seven interstitial THF molecules are found to ll the structural voids with no close contacts.…”
Section: Crystal Structures and Supramolecular Packingmentioning
confidence: 97%
“…The K/ O crown distances of 2.788(2)-2.832(2) A are comparable to those previously reported. [51][52][53][54][55] Two interstitial THF molecules were found in the crystal structure of 2$2THF, lling the structural voids with no close contacts.…”
Section: Crystal Structures and Supramolecular Packingmentioning
confidence: 99%
See 1 more Smart Citation
“…Though this may not be surprising for molecules such as the [N]phenylenes, which contain both aromatic and antiaromatic moieties, 11 we have also recently reported on similar behavior in an all-benzenoid molecule. 12 Beyond the fundamental interest into their electronic structure, accurate characterization of the aromatic behavior of PASs also has practical significance. Due to their stable low band-gaps, tunability, and structural features, PASs have long been the workhorses of organic electronics.…”
Section: Introductionmentioning
confidence: 99%
“…[9] Comprehensive studies of electron transfer for carbon bowls, [10] belts, [11] and wires [12] revealed a pronounced dependence on p topology and charge, opening a broad exploration of redox chemistry of curved and twisted molecular nanocarbons. [13][14][15] Recently, we have reported the first examples of chemical reduction of double [5]helicenes (Scheme 1 A and B). For the heteroatom-doped helicene A, an increasing twist of the carbon core upon two-electron charging was found along with the reversibility of reduction.…”
mentioning
confidence: 99%